The law of wills and intestacy in Malaysia - Halim, Akmal Hidayah; Mohd Salim, Wan Noraini; Abdul Hak, Nora; Mohd Kamal, Mohd Hisham (Department of Islamic Law & Harun M. Hashim Law Centre, 2009)
This book covers aspects of law of wills and intestacy as applied in West Malaysia. The main discussion focuses on the requirements for a valid will and also the law on intestacy in cases where a person dies without leaving a valid will. The aspect of estate administration is also discussed in order to highlight the importance of procedural law.